(untitled) (Jóvenes en la Ciencia, 2024)
In the work, two variants of audio input for the children’s book using Braille font "Kvasko and Katrusya", which is intended for partially sighted and blind children of primary school age, are investigated. In the first, specialized software is used to create an audiobook and announcers’ voices, in the second - text recognition of the prepared original layout and automatic generation of an audio file. In order to determine a more effective technology for the production of audio applications, an expert evaluation of these applications was conducted, and recommendations were developed for the use of multimedia technologies for inclusive editions.